(untitled) (Bangladesh Journal of Medical Education, 2020)
This descriptive type of cross-sectional study was carried out in 4 government and 4 non-government medical colleges of Bangladesh to assess the quality of undergraduate medical education. The study was conducted during the period of July 2018 to June 2019. The total sample size was 576, out of which there were 440 fifth year medical students, 114 clinical teachers and 22 Key informants. Convenience sampling technique was adopted. Two self - administered semi- structured questionnaires and one in-depth-interview schedule were utilized for the study. The study revealed that there was shortage of teaching staffs and infrastructure facilities. However numbers of hospital beds, indoor and outdoor patients were found to be sufficient. Study revealed that most of the students learned to take history, examine the patients; but had difficulties to make a provisional diagnosis. The clinical teaching in evening session was found to be neglected. Teachers could not ensure students’ learning of optimum skills and attitude. The study recommended reviewing the curriculum. Course burden should be reduced by removing redundant contents. The subjects namely Pathology, Microbiology and Pharmacology need to be rearranged to shift those to second phase. Emphasis is required to be given on behavioural science, communication skills and medical ethics. Bangladesh Journal of Medical Education Vol.11(2) 2020: 34-42